Impact of a TAK-1 inhibitor as a single or as an add-on therapy to riociguat on the metabolic reprograming and pulmonary hypertension in the SUGEN5416/hypoxia rat model - Morales-Cano, Daniel; Izquierdo-García, Jose Luis; Barreira, Bianca; Esquivel-Ruiz, Sergio; Callejo, Maria; Pandolfi, Rachele; Villa-Valverde, Palmira; Rodríguez, Ignacio; Cogolludo, Angel; Ruiz-Cabello, Jesus; Perez-Vizcaino, Francisco; Moreno, Laura (Frontiers in Pharmacology, 2023)
Background: Despite increasing evidence suggesting that pulmonary arterial hypertension (PAH) is a complex disease involving vasoconstriction, thrombosis, inflammation, metabolic dysregulation and vascular proliferation, all the drugs approved for PAH mainly act as vasodilating agents. Since excessive TGF-β signaling is believed to be a critical factor in pulmonary vascular remodeling, we hypothesized that blocking TGFβ-activated kinase 1 (TAK-1), alone or in combination with a vasodilator therapy (i.e., riociguat) could achieve a greater therapeutic benefit. Methods: PAH was induced in male Wistar rats by a single injection of the VEGF receptor antagonist SU5416 (20mg/Kg) followed by exposure to hypoxia (10%O2) for 21 days. Two weeks after SU5416 administration, vehicle, riociguat, the TAK-1 inhibitor 5Z-7-oxozeaenol, or both drugs combined (3mg/kg/day) were administered for 7 days. Metabolic profiling of right ventricle (RV), lung tissues and pulmonary artery smooth muscle cells (PASMCs) extracts were performed by magnetic resonance spectroscopy, and the differences between groups analyzed by multivariate statistical methods. Results: In vitro, riociguat induced potent vasodilator effects in isolated PA with negligible antiproliferative effects and metabolic changes in PASMCs. In contrast, 5Z-7-oxozeaenol effectively inhibited PASMC proliferation and metabolic reprogramming but had no acute vasodilator effects. In vivo, treatment with riociguat partially reduced the increase in pulmonary arterial pressure (PAP), right ventricular hypertrophy (RVH), and pulmonary vascular remodeling, attenuated the dysregulation of inosine, glucose, creatine and phosphocholine in RV and fully abolished the increase in lung IL-1β. By contrast, 5Z-7-oxozeaenol significantly reduced pulmonary vascular remodeling and attenuated the metabolic shifts of glucose and PC in RV but had no effects on PAP or RVH. Importantly, combined therapy had an additive effect on pulmonary vascular remodeling and induced a significant metabolic effect over taurine, amino acids, glycolysis, and TCA cycle metabolism via glycine-serine-threonine metabolism. However, it did not improve the effects induced by riociguat alone on PAP or RVH. None of the treatments attenuated pulmonary endothelial dysfunction and hyperresponsiveness to serotonin in isolated PA. Conclusions: Our results suggest that inhibition of TAK-1 induces antiproliferative effects and its addition to short-term vasodilator therapy enhances the beneficial effects on pulmonary vascular remodeling and RV metabolic reprogramming in experimental PAH.